Über das Verhältnis des Französischen zu den einheimischen Sprachen im postkolonialen Afrika: Eine Bestandsaufnahme - Yéo, Lacina (Stellenbosch Papers in Linguistics Plus, 2012)
Early intercultural contact occurred in West Africa through transatlantic slavery and colonisation. Thisled to the development of hybridized cultures in many parts of the world. Depending on the historicalcontext in different communities, this cultural hybridization has manifested itelf in linguistic formsand is currently central in post-colonical discourse. It is possible to trace current power relations andsocial hierarchies in a particular community back to the relationship between colonial languages(which in many cases are used as official languages, languages of business and languages ineducation) and the indigenous local languages (which were disregarded in colonial times). This paperconsiders how the relationship between French and indigenous African languages, in such a context, isto be estimated in various domains of use.Keywords Schlüsselbegriffe : Kolonialsprachen, afrikanische Sprachen, Postkolonialismus, sprachliche und kulturelle Hybridität: colonial languages, African languages, postcolonialism, linguistic and cultural hybridity